Second primary breast cancer after diagnosis of breast cancer among male patients: An examination of population characteristics and overall survival. (October 2020) - Chowdhry, Amit K.; Chowdhry, Divya N.; Shayne, Michelle; Milano, Michael T.
Abstract: Background: Male patients with breast cancer (BrC) have increased risk of developing 2nd-primary BrC (2nd-BrC). Given the relative rarity of male BrC, population-based registries are needed to analyze overall survival (OS) outcomes for these patients. Methods: Using the Surveillance, Epidemiology and End Results registry of patients diagnosed from 1975 to 2016, a cohort study of men whose only malignancy was BrC (BrCO; n  = 6, 475), and men who developed 2nd-BrC after initial BrC diagnosis (BrC-2; n  = 85) was performed. The standardized incidence ratio (SIR) of 2nd-BrC, Kaplan-Meier OS and multivariable Cox regression modelling were performed. Findings: The SIR for 2nd-BrC was 32.95 (95%CI:[23.85–44.38], p  < 0.05). The majority (88%) of 2nd-BrC for BrC-2 were contralateral from 1st-BrC; suggesting the unlikeliness of miscoding local recurrences as 2nd-BrC for most patients. There was no statistically significant difference between rates of hormone (reported in 44%) or HER-2 (reported in 33%) receptor status between BrC-O and BrC-2, albeit with limited data. The 2nd-BrC for BrC-2 was significantly more likely to be localized or distant stage (rather than regional) than BrC-O. Median OS was 103 months (95% CI: [99, 108]) for BrC-O and 62 months (95% CI [49, 128] after 2nd-BrC. When sub-grouped by BrC stage, and when analyzed by Cox regression, there was no significant difference in OS between BrC-O and BrC-2. Interpretation: Patients with male BrC are at significantly increased risk of 2nd BrC, but they can expect similar post-BrC prognosis (versus those without 2nd-BrC), after adjusting for patient demographics and tumor characteristics known to affect OS. Funding: None.